2009
DOI: 10.1371/journal.pone.0004174
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterisation of Cell-Type Specific Expression of CK1δ in Various Tissues of Young Adult BALB/c Mice

Abstract: BackgroundCasein kinase 1 delta (CK1δ) phosphorylates many key proteins playing important roles in such biological processes as cell growth, differentiation, apoptosis, circadian rhythm and vesicle transport. Furthermore, deregulation of CK1δ has been linked to neurodegenerative diseases and cancer. In this study, the cell specific distribution of CK1δ in various tissues and organs of young adult BALB/c mice was analysed by immunohistochemistry.Methodology/Principal FindingsImmunohistochemical staining of CK1δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…Immunohistochemical staining using two different CK1ε-specific antibodies confirmed the ubiquitous expression patterns of CK1ε. We observed a distribution pattern for CK1ε similar to that recently described for CK1y (Lohler et al 2009). This may not be surprising in view of the high homology between CK1y and CK1ε.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Immunohistochemical staining using two different CK1ε-specific antibodies confirmed the ubiquitous expression patterns of CK1ε. We observed a distribution pattern for CK1ε similar to that recently described for CK1y (Lohler et al 2009). This may not be surprising in view of the high homology between CK1y and CK1ε.…”
Section: Discussionsupporting
confidence: 86%
“…CK1ε is highly expressed in endocrine organs, pointing to an involvement in the production, storage, and/or secretion of hormones, as previously described for other CK1 family members (Gross et al 1997;Gross and Anderson 1998;Murakami et al 1999;Behrend et al 2000b;Knippschild et al 2005;Lohler et al 2009). We observed strong cytoplasmic CK1ε positivity in all three parts of the pituitary gland, indicating that CK1ε might be involved in specific functions of the SNARE complex and in neurotransmitter release, like CK1a and -y (Gross et al 1995;Shimazaki et al 1996;Reisinger and Allerberger 1999;Kataoka et al 2000;Pyle et al 2000;Chheda et al 2001;Dubois et al 2002;Snyder et al 2006;Wolff et al 2006;Pozzi et al 2008).…”
Section: Endocrine Tissuesupporting
confidence: 58%
“…One possibility is that cell type-specific expression of the two isoforms mediates the results. Although the general distribution of expression of Csnk1e and Csnk1d in the brain is similar, specificity of Csnk1e and Csnk1d expression has been observed in cell types such as Purkinje cells and astroglia (Utz et al, 2010;Lohler et al, 2009). Furthermore, a recent study showed that loss of DARPP-32 in D1-expressing cells reduced baseline and cocaine-induced locomotor activity whereas loss of DARPP-32 in D2-expressing cells increased baseline and cocaineinduced locomotor activity (Bateup et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previously carried out analyses of their cell-type specific expression in young adult mice revealed that both isoforms are highly expressed in adipocytes of white and brown adipose tissues (Lohler et al, 2009;Utz et al, 2010). Similarly, CK1δ and ε are expressed in the cytoplasm of adipocytes in human omental and subcutaneous adipose tissue (Fig.…”
Section: Expression Of Ck1δ and ε In Adipose Tissuementioning
confidence: 92%